Design and test of the bilateral throwing soil-covering device for straw mulching machine in orchards - Zhu, Xinhua; Gao, Xiang; Li, Xudong; Xu, Shaojie (International Journal of Agricultural and Biological Engineering, 2023)
Aiming to lack the function of soil covering in the developed orchard straw mulching machine (OSM), a kind of bilateral counter-throwing soil-covering device was developed to eliminate the orchard fire risk caused by the straw layer. The soil-covering device was suspended at the rear of the OSM. Its core component was a pair of throwing wheels installed on both sides of a frame. Hydraulic motors drove the throwing wheels to take soil on-site and cover the straw layer. The adjustment range of the space between the throwing wheels on both sides was 1.4-2.1 m. Based on analysis of soil-covering quantity, soil-covering width, thickness uniformity of soil layer, and power consumption, the key parameters such as the radius, number of the vane, and minimum rotation speed of the throwing wheels were determined. It was proved that the thickness uniformity of the soil layer by bilateral counter-throwing was better than by unilateral, and bottom throwing was better than top throwing. The blade of the soil cutter consisted of a straight blade and a curved blade, and the sliding-cutting angle was 14°-40°. The field test results showed the soil-covering device had good performance with a width of 1.4-2.2 m, a thickness of the soil-covering layer (TSL) of 23.2-40.7 mm, a standard deviation (SD) of 1.4-2.9 mm, width uniformity of 100%, and leakage rate of zero. The established model, between the thickness of soil-covering layer and trenching depth, throwing angle, and rotation speed of the throwing wheels, has a determination coefficient of 0.9757 and can be used to guide the operating parameters. The soil cutter reduced the power consumption and impact load of the throwing wheels by 64.77% and 60.88%, respectively. This work provides a type of new equipment for the mechanization technology of straw mulching in arid and semi-arid orchards.Keywords: orchard, straw mulching, mechanization, soil-covering device, counter-throwing, uniformityDOI: 10.25165/j.ijabe.20231601.7010Citation: Zhu X H, Gao X, Li X D, Xu S J. Design and test of the bilateral throwing soil-covering device for straw mulching machine in orchards. Int J Agric & Biol Eng, 2023; 16(1): 162–171.